Effect of Time and Curing Concentration on Quantity and Quality of Goat Skin Gelatin Produced by Acid Process - M. I. Said; J. C. Likadja; M. Hatta (Jurnal Ilmu dan Teknologi Peternakan, 2011)
Gelatin is widely used in food and non-food industries. One of its utilizations  in the food industry is as a biopolymer packaging materials to extend product shelf life. The quantity and quality of gelatin used is influenced by the production process, especially the curing period. This study aimed to determine the effect of curing time and concentration of curing agent  on the quantity and quality of gelatin produced from goat skin by acid process. Material used in this experiment was goat skin of Ettawah cross male, 1.5 to 3 years old.  The experiment was carried out in a 2x3 factorial arrangement according to completely randomized design with three replications for each treatment combination.  The first factor was curing time, i.e. 2 and 4 days and the second factor was the concentration of curing  agent, i.e. 3, 6 and 9%.  The gelatin was produced by the treatment with acetic acid (CH3COOH 0.5 M, v/v) as the curing  agent.  The results showed that application of CH3COOH 0.5 M with  concentration of 9% for 4 days yielded the best quantity and quality of gelatin, with product characteristics are yields of 16,39% and protein contents of  90.74%.